Children benefit from gestures to understand degraded speech but to a lesser extent than adults - Sekine, Kazuki; Özyürek, Aslı (Frontiers in Psychology, 2024)
The present study investigated to what extent children, compared to adults, benefit from gestures to disambiguate degraded speech by manipulating speech signals and manual modality. Dutch-speaking adults (N = 20) and 6- and 7-year-old children (N = 15) were presented with a series of video clips in which an actor produced a Dutch action verb with or without an accompanying iconic gesture. Participants were then asked to repeat what they had heard. The speech signal was either clear or altered into 4- or 8-band noise-vocoded speech. Children had more difficulty than adults in disambiguating degraded speech in the speech-only condition. However, when presented with both speech and gestures, children reached a comparable level of accuracy to that of adults in the degraded-speech-only condition. Furthermore, for adults, the enhancement of gestures was greater in the 4-band condition than in the 8-band condition, whereas children showed the opposite pattern. Gestures help children to disambiguate degraded speech, but children need more phonological information than adults to benefit from use of gestures. Children’s multimodal language integration needs to further develop to adapt flexibly to challenging situations where they hear the degraded speech, that was tested in the current study, speech with the environmental noise or the speech coming through a mask.